PENGARUH WORK LIFE BALANCE TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA BADAN INSPEKTORAT KABUPATEN KONAWE - Sri Widati (FEB Universitas Lakidende, 2019)
This study aims to determine and analyze empirically the effect of work life balance on employee performance with job satisfaction as an intervening variable in the Inspectorate Board of Konawe Regency. Operationally the work life balance variable is measured by five indicators, employee performance variable is measured by five indicators, and satisfaction variable Work is measured by five indicators. The population in this study were all employees of the Inspectorate Board of Konawe Regency. Total respondents were 50 people. Data taken from questionnaires distributed to respondents. Analysis of the data used in this research are: multiple regression test, t test, F test, determinant coefficient test, normality test and path analysis. The results showed that the results of the t work life balance test on the performance of employees with t count work life balance of 2.057 greater than 1.887 and significant 0.033, which means the equation of both shows the value of t count work life balance of 0.344 smaller 1.879 with a significant 0.656 which means work life balance has no direct effect with job satisfaction as an intervening variable with t count for job satisfaction of 4.072, greater than 1.887 and significant 0.000, which means job satisfaction has a significant effect on employee performance.